Acceleration of crystal transformation from crystal form II to form I in Polybutene-1 induced by nanoparticles. (15th August 2018) - Zhang, Xing-Xing; Li, Yan-Kai; Sun, Zhao-Yan
Abstract: The influence of nanofillers on the crystal transformation from crystal form II to form I of isotactic polybutene-1(PB-1) was investigated by differential scanning calorimetry (DSC), in situ wide-angle X-ray diffraction (WAXD) and small-angle X-ray scattering (SAXS) techniques. Two types of silicate clay both having one-dimensional structure, halloysite nanotube (HNT) and palygorskite (PGS), were used as nanofillers of PB-1. PGS accelerates the transformation from crystal form II to I for PB-1 more efficiently than HNT, which is attributed to the lattice match of crystal structure between PGS and form I as confirmed by the WAXD and SAXS tests. Moreover, hydrophobically modified clays MPGS and MHNT were used to improve the miscibility between nanoparticle and PB-1. However, transformation kinetics study indicates that the acceleration effect of MPGS is greatly decreased due to the shield of lattice match although the miscibility of the composites is improved, while that of MHNT is increased due to the improvement of miscibility. These results provide direct evidence that the existence of crystallographic relationships is another important factor to accelerate the crystal transformation from form II to I in PB-1. Graphical abstract: Image 1 Highlights: The crystal transition from form II to form I in PB-1 can be accelerated by introducing a suitable nanofiller. Crystallographic relationship between nanoparticles and form I will dominate the transition from form II to form I in PB-1. Hydrophobically modification on PGS will reduce the acceleration effect due to the shield of lattice match.